The Uses of the Baobab Flower (Adansonia digitata L) - Rashford, John (Ethnobotany Research and Applications, 2015)
In the now extensive literature on the African baobab, the use of the flower is often overlooked or described as minimal. This paper presents a synthesis of the uses of the baobab flower that incorporates the results of my own fieldwork on the introduction and cultural significance of the baobab in Florida, the Caribbean, and Brazil. Fieldwork conducted over the past 30 years has involved locating, measuring, and photographing baobabs; observations on flowering and fruiting and such things as the size and shape of fruits and the number of seeds per fruit; and structured and unstructured interviews and community discussions to determine the cultural significance of the tree. In addition to publications and word of mouth, baobabs were also located by appeals to the public involving newspaper interviews and radio interviews. Although the uses of the baobab flower have yet to be documented in a manner comparable to other parts of the tree—especially the fruit, leaves, and bark—the present study shows it is far from being useless or of little use as some premature assessments would suggest. This initial summary is intended to encourage greater attention to the uses of the flower in the increasingly sophisticated research on the baobab that is now being done in Africa and elsewhere. En la literatura del baobab africano, hoy en día extensa, el uso de la flor a menudo se pasa por alto o se describe como mínimo. Este artículo presenta una síntesis de los usos de la flor del baobab que incorpora los resultados de mis estudios en el campo relativos a la introducción y el significado cultural del baobab en Florida, el Caribe y en Brasil. El trabajo de campo realizado en los últimos 30 años se ha dedicado a localizar, medir y fotografiar baobabs; a hacer observaciones de la floración y la fructificación y de cosas como el tamaño y la forma de los frutos y el número de semillas por fruto; a llevar a cabo entrevistas estructuradas y no estructuradas, así como conversaciones con la comunidad para determinar el significado cultural del árbol. Además de las publicaciones y referencias verbales, también se localizaron baobabs por medio de llamados al público en entrevistas radiales y en periódicos. A pesar de que los usos de la flor del baobab aún están pendientes de documentarse en forma comparable a las otras partes del árbol—especialmente el fruto, las hojas y la corteza—el presente estudio muestra que, contrario a lo que valoraciones prematuras sugieren, la flor está lejos de ser de poca o ninguna utilidad. Este extracto inicial pretende atraer más atención a los usos de la flor en la investigación del baobab, la cual es cada vez más sofisticada y que ya se realiza en África y en otras latitudes.